Henning Høirup: Fra døden til livet - Grundtvigs tanker om liv og død - Balslev, Th (Grundtvig-studier, 1954)
Henning Høirup. From Death to Life. By Th. Balslev. This book, which discusses the antithesis that constitutes the central problem in all Grundtvig’s writings, the antithesis between death and life, is the fruit of a series of lectures which Dr. Høirup delivered at Aarhus University in the autumn of 1953 at the request of “the Church School” (Kirkeskolen). We can only be thankful that this discussion, which is so thorough and at the same time so easy to follow in spite of the frequent use of technical terms, has not been reserved for a smaller circle. It contains much material which is new even for those who thought themselves quite at home in Grundtvig’s world af ideas. For Grundtvig life and death are not merely biological phenomena, but the two fundamental powers which are constantly at war. Grundtvig freed himself early from the monistic theories of Romanticism, thanks to his mythological studies which enabled him to apprehend, in the struggle of life with the powers of death, the truth of the Christian doctrine concerning the dualism in existence, and in the next place through Luther, and not least through Irenæus who, in particular, maintains that true life is fellowship with God and death separation from God. In opposition to Prof. Hal Koch, who recently asserted that Grundtvig, in contrast to Luther, did not fully understand the relationship between man and death but was influenced in regard to this point by the attitude of the 19th century, Dr. Høirup adduces evidence to show that Luther and Grundtvig are entirely at one in believing that death is eternal separation from God and our neighbour, and that eternal death is the work of the Devil, from which Christ has freed us by His death on the cross. Like Luther, Grundtvig talks of bitter death. It is doubtful, however, whether Dr. Høirup is right in stating that Grundtvig borrowed the expression from Luther. It is found in hymns and in the Old Testament (1. Sam. 15,32 and Sirach, 41,1), and undoubtedly was also commonly used in popular speech. Dr. Høirup shows that neither Luther nor Grundtvig always avoided contradictions in what they said about death. Grundtvig dissociates himself from the conception of “a blessed death” (which was used especially by Luthers fellowers), because eternal life is here and now, too; but he can occasionally use vague expressions of comfort in face of death, in the confidence that Christ has overcome the death which would seperate us from God for ever. But at other times death fills him with a horror which finds its deepest and most impressive expression in the hymn “at sige Verden ret Farvel” ( “ To bid the world farewell aright”). And it is certain that Grundtvig was miles apart from the conception of death as a friend, which is found in “ Evangelisk-christelig Psalmebog” (The Evangelical Christian Hymn-book) and which receieved its classical expression in Pram’s verse: “O friendly grave, in thy shade there is peace.” Dr. Høirup rightly stresses the point that to renew the teaching of the Gospel about death and resurrection was a matter very near to Grundtvig’s heart. Another valuable thing in Dr. Høirups book is his account of Grundtvigs ideas about the relation between the spoken and the written word, which are here compared with the related ideas of other students of language, while attention is likewis directed to his agreement (in this connection also) with Luther, which has hitherto been little noticed. (In this connection it may also be remembered that a High Church theologian like Martensen accepted Grundtvig’s conception of “the spirit and the world of the spirit as the only reality . . . and of the world of power, when it gives itself living utterance among the powers of life.”) This little book, which also deserves commendation for opposing modern claims that Grundtvig, in contrast to Luther, did not realise the importance of man’s relation to his neighbours, shads new light and gives a clearer understanding of Grundtvig’s philosophy of life, and will strengthen and confirm those who already felt themselves fairly well at home in this philosophy. It is a good book.